Longer‐term impact of COVID‐19 among individuals with self‐reported eating disorders in the United States, the Netherlands, and Sweden. Issue 1 (13th October 2022) - Termorshuizen, Jet D.; Sun, Quan; Borg, Stina; Mantilla, Emma F.; Goode, Rachel W.; Peat, Christine M.; Thornton, Laura M.; Watson, Hunna; van Furth, Eric F.; Birgegård, Andreas; Bulik, Cynthia M.
Abstract: Objective: We assessed eating disorder (ED) illness status, symptomatology, treatment access, anxiety, and depression in the first year of the COVID‐19 pandemic among individuals with a pre‐existing ED in the United States (US), the Netherlands (NL), and Sweden (SE). Methods: Participants completed online surveys in April–July 2020, at the early stage of the pandemic, and one year later. At one‐year follow‐up, we added questions addressing retrospective changes in ED symptoms, treatment, and anxiety/depression since the start of the COVID‐19 pandemic. We present descriptive statistics and assess change in ED symptomatology, treatment, and anxiety/depression among those with an active or lingering ED. Results: Participants (US n = 132; NL n = 219; SE n = 702) were mostly young and female with a history of anorexia nervosa (>60% in all three countries). Across countries, respondents reported impact of COVID‐19 on ED symptoms at both time points, with improvement in US and NL at one‐year follow‐up, and stable but less impact on ED symptoms in SE. Furthermore, at one‐year follow‐up, roughly half of those in treatment reported reduced treatment access and quality, and the majority of the sample reported increased anxiety and depressive mood since the start of the pandemic. Discussion: Our findings suggest that the self‐perceived impact of COVID‐19 changed over time but remained concerning even one year after the start of the pandemic. Clinicians, community organizations, and policy makers are encouraged to address potentially changing treatment needs in the face of public health emergency events. Public Significance: Our findings suggest that the impact of COVID‐19 on individuals with eating disorders decreased over time but remained concerning even one year after the start of the pandemic and that the impact differed across countries. Clinicians, community organizations, and policy makers are encouraged to incorporate this knowledge to address potentially changing treatment needs in the face of public health emergency events.